Characteristics of the pseudorabies virus strain GDWS2 with severe neurological signs and high viral shedding capacity in pigs - Chen, Wang; Fan, Gao; Huang, Yurong; Zhou, Keyue; Chen, Zifan; Chen, Kexin; Zhang, Huihua; Li, Zhaoyao (Frontiers in Veterinary Science, 2025)
Pseudorabies virus (PRV) poses a serious threat to the global swine industry, as PRV infection can lead to reproductive disorders in sows and high mortality in newborn piglets. Although pigs typically exhibit age-related resistance to PRV, with older pigs exhibiting milder symptoms upon infection, the recent isolation of multiple highly pathogenic PRV variants and reports of severe symptoms and even death in older pigs have garnered much attention. The GDWS2 strain isolated in this study exhibits characteristics similar to those of highly pathogenic strains. GDWS2 was isolated from the brain tissue of a 90-day-old diseased pig that exhibited severe respiratory and neurological symptoms. The pig originated from a farm that had been previously vaccinated with the Bartha-k61 strain. In vitro experiments demonstrated that GDWS2 induces substantial cytopathic effects in PK-15, VERO, BHK cells, and PAM. Moreover, GDWS2 formed larger plaques and exhibited higher early replication titers in PK-15 cells compared to the highly pathogenic variant strain JM isolated in China. Phylogenetic analysis revealed that GDWS2 belongs to PRV genotype II, with gD, gE, and TK genes showing high homology to those of highly pathogenic PRV variants. Additionally, GDWS2 harbors unique insertions or mutations in the US1, UL36, and UL5 gene regions, and its genome contains recombination events with PRV variants, Bartha, or genotype I strains. In vivo experiments further confirmed the high pathogenicity of GDWS2. In rabbit and 90-day-old pig models, GDWS2, compared with the JM strain, caused high mortality rates, accompanied by severe pathological damage. Notably, in the 90-day-old pig model, the GDWS2 challenge group exhibited more severe respiratory and neurological symptoms, and enhanced neurotropism and shedding capacity. The data from this study may indicate the emergence of a naturally recombined and highly pathogenic PRV variant in China once again.